Factors Associated with Mortality of Lambs Born to Ewe Hoggets - Ridler AL; Flay KJ; Kenyon PR; Blair HT; Corner-Thomas RA; Pettigrew EJ (MDPI (Basel, Switzerland), 2022)
The reproductive performance of ewe hoggets is poorer than that of mature-age ewes due to production of fewer lambs with poorer survival. Scant data are available on the risk factors for, and causes of, the mortality for lambs born to ewe hoggets, the impact of ewe deaths on lamb loss, and the causes of death for lambs born to ewe hoggets vs. mature-age ewes lambing in the same circumstances. In this study, 297 lambs born to 1142 ewe hoggets were necropsied along with 273 lambs born to 1050 mature-age ewes. Low lamb birthweight, multiple litter size, and increasing ewe hogget average daily gain from breeding to late pregnancy were risk factors for lamb mortality. The most common cause of mortality for lambs born to ewe hoggets was stillbirth and the risk factors for stillbirth were similar to those for lamb mortality generally. Approximately 11% of ewe hoggets’ lamb deaths were due to the death of the dam. Causes of mortality differed between lambs born to ewe hoggets vs. those born to mature-age ewes. Management practices to increase ewe hogget lambs’ birthweights (particularly those from multiple litters) and supervision of ewe hoggets at lambing time are recommended.
Keywords: body condition score; dystocia; ewe; hogget; lamb; mortality; reproduction; stillborn; survival; vaginal prolapse